Right ventricular dilatation after left ventricular acute myocardial infarction is predictive of extremely high peri-infarctual apoptosis at postmortem examination in humans. Issue 9 (27th August 2003) - Bussani, R; Abbate, A; Biondi-Zoccai, G G L; Dobrina, A; Leone, A M; Camilot, D; Di Marino, M P; Baldi, F; Silvestri, F; Biasucci, L M; Baldi, A
Abstract : Background: Cardiac remodelling after acute myocardial infarction (AMI) is characterised by molecular and cellular mechanisms involving both left and right ventricles, and biventricular failure identifies patients with an extremely unfavourable prognosis. Aims: To assess whether a link exists between increased myocardial apoptotic rates (AR) at sites of recent infarction and patterns of unfavourable cardiac remodelling, such as biventricular enlargement after left ventricular (LV) infarction. Methods: Twelve patients with recent AMI involving the LV and not the right ventricle (RV) and with permanent infarct related artery occlusion were selected at necropsy. Gross pathological characteristics, such as LV and RV dilatation, and AR at site of infarction were assessed. Potential false positive results (DNA synthesis and RNA splicing) were excluded from the cell count. Results: RV enlargement, defined as a tricuspidal ring greater than 120 mm, was found in five cases and was associated with LV dilatation. These patients showed significantly higher AR than the others. When the subjects were divided into three groups according to progressive cardiac remodelling (absence of cardiac dilatation, isolated LV dilatation, and biventricular enlargement), the last group had significantly higher ARs than the other two groups, showing that myocardiocyte apoptosis is increased in more unfavourable forms of cardiac remodelling. Conclusion: Patients with severely unfavourable cardiac remodelling, such as biventricular enlargement, have extremely high myocardiocyte apoptosis at necropsy, even late after LV myocardial infarction, supporting the role of myocardiocyte loss in determining post-infarction adverse remodelling.